Analisis Kinerja Protokol MQTT dan HTTP Pada Akuisisi Data Magnet Berbasis Internet of Things - Hairatunnisa Hairatunnisa; Hapsoro Agung Nugroho; Relly Margiono (Jurnal Ilmiah Informatika, 2021)
One of the determinants of the quality of magnetic data is continuous data, so we need a data transmission system that can continuously transmit observational data. In this research, a magnetometer communication system design was carried out with the concept of the Internet of Things (IoT) using the MQTT and HTTP protocol, where measurement data in the form of the x-axis, y-axis, z-axis, horizontal components, and total magnetic field components are displayed on the dashboard in real time and continuously. Testing the performance of sending data is done using the Wireshark, it is known that the MQTT protocol has a better delivery quality compared to the HTPP protocol with an average delay value of 0.0120 seconds, an average value of packet length of 54 bytes and a packet loss value of 0.11%, while the HTTP protocol has an average delay value of 0.0257 seconds, an average packet length value of 268.1 bytes and a packet loss value of 0.5%.